2020
DOI: 10.1017/9781108761338
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Public Performance

Abstract: A revolution in the measurement and reporting of government performance through the use of published metrics, rankings and reports has swept the globe at all levels of government. Performance metrics now inform important decisions by politicians, public managers and citizens. However, this performance movement has neglected a second revolution in behavioral science that has revealed cognitive limitations and biases in people's identification, perception, understanding and use of information. This Element intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 178 publications
0
33
0
2
Order By: Relevance
“…First, this study adds to scholarly work on Public Value Governance, which explicitly calls for more empirical research into how diverse government actors deal with the assessment of (public) values for given policy issues (e.g., Bozeman 2019;Bryson, Crosby, and Bloomberg 2014;Fukumoto and Bozeman 2019;Hartley et al 2017;Nabatchi 2012;Huijbregts, George, and Bekkers 2021). Moreover, this study adds to scholarly work on Behavioural Public Administration, which explicitly calls for more empirical research into how political decision-making is impacted by different strategy and performance tools (e.g., George 2020; James et al 2020). Second, this study employs a vignette-based, randomized survey experiment among actual local politicians in Flanders, Belgium, to infer causality concerning the impact of valuation tools on political decision-making.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…First, this study adds to scholarly work on Public Value Governance, which explicitly calls for more empirical research into how diverse government actors deal with the assessment of (public) values for given policy issues (e.g., Bozeman 2019;Bryson, Crosby, and Bloomberg 2014;Fukumoto and Bozeman 2019;Hartley et al 2017;Nabatchi 2012;Huijbregts, George, and Bekkers 2021). Moreover, this study adds to scholarly work on Behavioural Public Administration, which explicitly calls for more empirical research into how political decision-making is impacted by different strategy and performance tools (e.g., George 2020; James et al 2020). Second, this study employs a vignette-based, randomized survey experiment among actual local politicians in Flanders, Belgium, to infer causality concerning the impact of valuation tools on political decision-making.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, by means of these tools, elected officials can legitimize their decision-making behaviour (Carpenter and Krause 2012;Coicaud 2002). Importantly, these assumptions concerning the rationality ensuing from using valuation tools are strongly contested on the basis of insights from behavioural science (George 2020;James et al 2020), which indicate the existence of cognitive biases among politicians (e.g., Battaglio et al 2019;. Despite these conflicting perspectives on the impact of valuation tools, little causal evidence can be found on the decision-making consequences of valuation tools among elected officials.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent performance management research has found that effective performance management requires appropriate performance routines as well (Behn 2010 ; Gerrish 2016 ; James et al 2020 ; Kroll and Moynihan 2018). Performance routines such as goal‐setting processes, performance budget negotiations, and performance reviews “structure how [actors] experience their work” (March and Simon 1993 ), help actors to make sense of ambiguity (Noordegraaf 2017), and motivate them to improve performance (Moynihan and Kroll 2016 ).…”
Section: Advancing Collaborative Performance Managementmentioning
confidence: 99%
“…To better understand the effects of ubiquitous public sector performance systems, Moynihan and Pandey (2010) proposed treating performance information (PI) use as a “big question” for researchers to address. Over the past decade, researchers have amassed an impressive body of evidence (James et al, 2020). The next logical question is whether performance information use makes a difference to organizational performance.…”
mentioning
confidence: 99%
“…However, PI use may not improve organizational performance for a number of reasons, such as goal ambiguity (Chun & Rainey, 2005; Moynihan, 2008), political constraints on managerial autonomy (O’Toole & Meier, 2011), difficulty in inferring what the data actually suggests about concrete actions (Moynihan, 2008), and cognitive biases (James et al, 2020). Hence, using PI has been found to be associated with null average effects at public organizations (Gerrish & Spreen, 2017; Hvidman & Andersen, 2014).…”
mentioning
confidence: 99%